Amyotrophic Lateral Sclerosis and Multiple Sclerosis: More Evidence Suggesting a Link - Pocock, Kristyn; Baysal, Idil; Scanlan, James; Elliott, Michael; Mayadev, Angeli (RRNMF Neuromuscular Journal, 2021)
Objectives Previous reports of the concurrence of multiple sclerosis (MS) and amyotrophic lateral sclerosis (ALS) in the same patients suggest shared pathogenesis, with the C9orf72 mutation as a possible shared genetic link.Methods: Symptoms, neuroimaging, and laboratory data were summarized for patients with ALS and MS within our ALS registry.  Using age adjusted MS prevalence rates, we calculated the expected co-occurrence using the binomial test. Results: Clinical and demographic features of the five patients (four female, one male) with ALS and MS are described.  Because ALS more frequently occurs in men, observing 4/5 female patients with concurrent ALS/MS showed a borderline expectation difference (P=0.073).  The observed co-occurrence of ALS and MS was 5X times higher than the expected frequency of 0.98 (P